An Observational Study on Use of Intravenous Paracetamol for Closure of Patent Ductus Arteriosus in Newborns - Dhungana, Diwas; Shrestha, Manish; Joshi, Suchita (Nepal Mediciti Medical Journal, 2021)
Introduction: Failure or delay in spontaneous closure of ductus arteriosus is commonly seen among very low birth weight and very preterm neonates (